Peluang Pasar Metaverse Tourism Pada Objek Wisata Museum Di Jakarta - Rizki Nugraha; Anisa Purwati (Peneliti.net, 2023)
This research examines how the metaverse market opportunities in tourist attractions at museums in Jakarta. The purpose of this research is to find out and study how the development of the tourism metaverse in Indonesia and how the metaverse market opportunities are at the Museum in Jakarta. The research method used is a literature study method with library data collection, reading and recording, and processing of research materials. The results showed that the development of the Metaverse in the Tourism industry provides a sense of satisfaction to tourists, where tourist satisfaction is a benchmark for success for every business actor in the tourism service business. The metaverse business opportunity at the Museum in Jakarta is very good, with the application of metaverse technology such as Virtual Augmented (VR) and Augmented Reality (AR) expanding museum visitors and a profitable market opportunity.